Studi Perhitungan Benchmark Kritikalitas Teras Metalik dan MOX di FCA - Zuhair Zuhair; Tagor M. Sembiring; Putranto Ilham Yazid (Lambung Mangkurat University Press, 2011)
The criticality experiments at FCA three cores have been done to obtainreliable original data as a benchmark test. The first two cores was mock-up of metallicfueled LMFBR’s and the other was a mock-up of a MOX fueled LMFBR. The criticalitycalculation of FCA cores was performed by using the Monte Carlo transport codeMCNP-4C in 2-D R-Z reactor geometry. The analysis was done with ENDF/B-VIcontinuous energy neutron cross-section library at room temperature. The MCNP-4Ccriticality prediction (keff) for metallic (XVI-1 and XVI-2) cores were underestimated in0.54% and 0.48%, respectively. The MCNP-4C criticality prediction (keff) for MOX(XVII-1) core showed best agreement with the experimental data where C/E value was0.99995. In general, it can be concluded that MCNP-4C calculations on FCA criticalitybenchmark experiments show a high accuracy for metallic as well as MOX cores.